Complications of radical cystectomy for bladder cancer - Gurram, Maliikarjuna; G., Ravichander; Jahagidar, Ravi; Reddy, Vinay (International Journal of Research in Medical Sciences, 2018)
Background: Radical cystectomy with pelvic lymph node dissection is the standard treatment for muscle-invasive bladder cancer. With the advent of improved surgical techniques and postoperative management, the complications and mortality rates have reduced. The present study was done to analyse the perioperative, early and late compilations following radical cystectomy for bladder tumor. Methods: This is a prospective observational study of patients who underwent radical cystectomy for invasive bladder tumor from February 2016 to November 2017. Radical cystectomy was done through midline transperitoneal approach. Urinary diversion was done by ileal conduit. All patients were followed at 6th week, 3rd month, 6th month, and at 1 year. Results: Total 21 patients underwent radical cystectomy, 17(80.95%) were males and 4 (19.04%) females. The median age was 60 years, ranging from 40 to 73 years. The most common age group was 60 to 75 years (52.3%). Thirteen (61.9%) patients were smokers and all were males. Painless haematuria alone was most common presentation (of bladder tumor) seen in 15 (71.4%) patients. Early complications were seen in 8 (38.09%) patients, most common early complication was urinary leak 2 (9.5%) patents, other early complications were bowel leak, wound dehiscence, pelvic collection, burst abdomen, prolonged ileus, subacute intestinal obstruction, acute kidney injury and sepsis seen in one (4.25%) patient each. Late complications were seen in 4 (19.04%) patients. Pelvic recurrence was the most common late complication seen in 2 (9.55%) patients. Ureteric stricture was seen in one patient (4.75%) for which percutaneous nephrostomy and antegrade DJ stenting was done. Among the histopathological variants of tumor 20 (95.25%) patients had high grade variants and only one (4.75%) had low grade papillary urothelial carcinoma. Among the high grade variants most common pathology was urothelial carcinoma in 17 (80.9%) patients. Conclusions: Radical cystectomy remains the main stay of treatment in muscle-invasive bladder cancer. This is relatively safe procedure with minimal morbidity and mortality.